Akulturasi Budaya Bugis dengan Islam dalam Tradisi Barzanji di Sulawesi Selatan - Dian Rizki Amalia (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2021)
This writing aims to find out the customs that exist in the region of South Sulawesi. Barzanji is a tradition found in the region of South Sulawesi (bugis -Makassar) barzanji is a prayer or praise of the story of the Prophet Muhammad, where there is a rhythm or melody that is sung at the birth of the Prophet Muhammad. Barzanji hails from a place in Kurdistan that was set up to increase love for the Prophet Muhammad SAW and also as a form of Islamic acculturation to unify local customs. This tradition is still widely practiced in Makassar because it has many meanings. The type of research used in this writing is qualitative descriptive by using library research methods and looking for other sources and to consolidate and clarify the results of observations. Keywords: meaning, barzanji, tradition, history.